Dolomites in a carbonate-evaporite system: the fifth member of the Middle Ordovician Majiagou Formation, Eastern Ordos Basin, China - Siyi Fu; Chenggong Zhang; Hao Liu; Liubin Wei; Hongping Bao; Xingchao Ye; Zhongtang Su; Hongde Chen; Liangbiao Lin (Frontiers in Marine Science, 2025)
Introduction The carbonate-evaporite system contains substantial hydrocarbon resources and serves as an excellent subject for studying dolomitization problem. In the Ordos Basin, the fifth member of the Ordovician Majiagou Formation have extensive carbonate-evaporite deposits. Methods This study utilizes extensive drilling data, thin section microscopic examination, scanning electron microscopy, and a variety of geochemical analyses to investigate the origins of evaporites and the genesis of dolomites within this formation. Results Our findings indicate that the fifth member of the Majiagou Formation primarily contains two types of evaporites (halite and anhydrite) and five types of dolomites: micritic (Dol-1), fine-crystalline fabric-obliterative dolomite (Dol-2), fabric-retentive dolomite (Dol-3), microbial mats-associated dolomite (Dol-4), and medium–coarse crystalline dolomite (Dol-5). The evaporites, originating from seawater (sulfur isotope compositions ranging from 23.0 to 27.9 ‰), exhibit a planar distribution controlled by paleotopography and evaporation intensity, with distinct deposition centers for gypsum and halite. The eastern part of the study area is dominated by halite deposits, while both gypsum and halite are developed in the central region, and the western part is primarily characterized by gypsum deposition. LA-ICP-MS data indicate varying concentrations of MgCO3 (34.4-44.3 wt%) and CaCO3 (45.4-58.9 wt%), as well as trace elements including Na, Al, Si, K, Cu, Ba, Mn, and Fe. REE patterns and δCe/δEu anomalies provide insights into dolomitization mechanisms. Discussion The formation of dolomites occurred in distinct stages. The first stage, from the penecontemporaneous to shallow burial periods, the formation of Dol-1, Dol-2, and Dol-3 through seepage-reflux dolomitization and evaporative pumping. Dol-4 also formed during this stage, closely associated with microbial dolomitization and influenced by tidal transport. The second stage, during deep burial, resulted in Dol-5, which can be further categorized into Dol-5-1, formed by continued dolomitization from pore fluids, and Dol-5-2, formed through hydrothermal processes. The intensity of dolomitization is closely linked to the distribution of evaporites. Carbonates underlying gypsum strata exhibit a higher degree of dolomitization compared to those beneath halite strata. This is due to gypsum absorbing Ca 2+ and releasing high-salinity brine during its transformation to anhydrite, thereby increasing the Mg 2+ /Ca 2+ ratio in formation fluids. Consequently, the hydrocarbon resource potential of carbonate strata beneath gypsum layers is likely higher than that of those beneath halite layers.